2019
DOI: 10.1111/asj.13265
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and lying behavior of milking Holstein cows at commercial tie‐stall dairy farms

Abstract: The aim of this study was to clarify cow's sleep behavior on farm and to examine the influence of some environment and management factors on cow's sleep. Total 85 behavior data (summer 41, autumn 44) were corrected from 12 commercial tie‐stall dairy farm in northern Tohoku area. Daily duration, bout frequency, and averaged bout duration of sleep and lying were measured. Even though there was no significant difference in any lying measurements, daily duration, bout frequency, and averaged bout duration of sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This progression may be a result of the reproductive cycles, the milk yield, the pasture management including grazing times and mosquito plagues or temperature and the climate. Cows also lie down less in summer when temperature increases [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This progression may be a result of the reproductive cycles, the milk yield, the pasture management including grazing times and mosquito plagues or temperature and the climate. Cows also lie down less in summer when temperature increases [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ninomiya and Sato (2009) suggested that behavioral satisfaction due to environmental enrichment can promote the daily sleep duration of Japanese black steers; however, they could not examine which enrichment treatment significantly influenced sleep. In our previous study (Fukasawa, Komatsu, & Higashiyama, 2019), there were significant differences in sleep posture measurements among commercial dairy farms, which had differences in managements such as diet and ventilation. However, we could not find any significant effects of management on sleep posture measurements because of small number of samples and confounding among management systems.…”
Section: Introductionmentioning
confidence: 91%